Propuesta de Mejora del Sistema de Gestión de Mantenimiento en la Empresa Transportliquidos S.A.S (2022)
The purpose of this research is to propose an improvement proposal for the maintenance management system in the company Transportliquidos S.A.S, it was carried out in three stages: a diagnosis that puts the current situation in the maintenance area into context and identifies opportunities for improvement; an analysis of information, with which the maintenance area is evaluated and the aspects to be improved are established. Transportliquidos S.A.S, is a company dedicated to the transport of liquids, mainly hydrocarbons and their derivatives, where its main client is Ecopetrol, for the provision of this service it has a fleet of 44 system-type heavy-duty trucks, which are managed in its headquarters in Villavicencio Meta, headquarters in which the management of their maintenance is carried out, the company has a headquarters in Sabaneta Antioquia from which the accounting and general management are handled. Among the results obtained, it was found that although the company does not have a maintenance workshop, it is necessary to implement several management tools such as: a purchasing management system, a control panel, the implementation of maintenance plans per vehicle. and a direction towards the implementation of a reliability centered maintenance (RCM) methodology. The proposal includes a clear description of how the implementation of this methodology should be through the example of its own maintenance management process